Publication practices in the Humanities: An in-depth case study of a Swedish Arts and Humanities Faculty 2010-2018 - Hansson, Joacim; Tyrkkö, Jukka; Golub, Koraljka; Ahlström, Ida (Nordic Journal of Library and Information Studies, 2021)
This paper is a case study of research publication practices at the Faculty of Arts and Humanities at Linnaeus University, a young, mid-sized university in the south-east of Sweden. Research output was measured from publications in the local institutional repository following the guidelines of local research policy as defined in university documentation. The data collection comprised 3,316 metadata records of publications self-registered by authors affiliated with the faculty during the period of 2010–2018. A statistical analysis of research output was conducted, focusing on preferred publication types, disciplinary specificity, level of co-authorship, and the language of the publication as registered in the local repository. The analysis focused on two main research questions: 1) how do the local research practices stand in relation to traditional publication patterns in the humanities? 2) how do the observed publication patterns relate to local university policy on publication and research evaluation? The empirical results suggest a limited correlation between publication practices and research incentives from university management, a finding that is corroborated by previous research on the scholarly character of the humanities and university policies. Overall, traditional humanities publication patterns were largely maintained throughout the period under investigation.